Spatial skills of preschool children from Serbia and a possible model for the typology of children’s spatial skills - Đokić, Olivera J.; Vorkapić, Marija M. (Frontiers in Education, 2024)
Introduction In their study, the authors delve into the impact of preschool curriculum on the spatial abilities development of children. They specifically explore the significance of spatial understanding through Piaget’s primacy of topological concepts and the increasing emphasis on projective geometry. The research focuses on preschoolers in Serbia, aged 5.5–6.5, as they transition to primary school. Methods The study involves 103 children exposed to two distinct preschool curricula: The General Foundations of the Preschool Curriculum (GFPC) and The Foundations of the Preschool Curriculum – Years of Ascent (YA). Drawing on the typology of spatial tasks in the 2 × 2 matrix, the researchers conducted individual structured interviews comprising 8 tasks. These tasks were designed to assess children’s performance across four sub-domains: Intrinsic–Static, Extrinsic–Static, Intrinsic–Dynamic, and Extrinsic–Dynamic. Results The findings reveal a general poor performance in solving spatial tasks among the children. Despite inconsistent results in the cognitive structures of spatial ability, the study indicates that the type of preschool program or gender does not significantly influence preschoolers’ spatial abilities in Serbia. Notably, differences were observed in the sub-domains of Static and Dynamic. However, the analysis suggests that the 2 × 2 model may not be an appropriate fit for the Serbian sample. Discussion The authors acknowledge the limitations of the 2 × 2 model and propose further exploration of alternative typologies to better characterize children’s spatial skills development in Serbia. They advocate for a model that accurately describes preschoolers’ spatial abilities and can inform curriculum creators in enriching mathematics education. The study underscores the importance of spatial reasoning for success in STEM fields, as supported by meta-analyses of children’s spatial abilities.